The low-grade basement at Península La Carmela, Chilean Patagonia: new data for unraveling the pre-Permian basin nature of the Eastern Andean Metamorphic Complex - Rojo, D. (2021)
The Eastern Andean Metamorphic Complex at Península La Carmela (48°50’S) consists of quartz-rich metaturbiditic sequences with tectonic slices of pillow metabasalt bodies deformed under low-grade metamorphic conditions. Previous and new detrital zircon U–Pb geochronological data from metasandstones indicate a preferred early Carboniferous maximum depositional age of the protolith, interpreted from the youngest single zircon grains of several metasedimentary rocks in the area. The wide spectrum of zircon ages from Península La Carmela, includes Neoproterozoic-early Paleozoic components and subordinate ancient zircon grains (> 2200 Ma). They were sourced from cratonic regions and/or reworked material from older metasedimentary successions and plutonic belts in southwestern Gondwana (e.g., North Patagonian and Deseado massifs or from the Tierra del Fuego Igneous and Metamorphic Complex). The pillow metabasalts have geochemical affinities of normal mid-oceanic ridge basalts and island-arc tholeiites with Nb–Ta negative anomalies, derived from a depleted mantle source (εNdt of + 6 and + 7.5). In consideration that pillow metabasalts with ocean island basalt affinities are reported, we propose that metaturbiditic successions and metabasalts were tectonically juxtaposed within a pre-Permian accretionary wedge of an active continental margin, after the development of island arcs and back-arc marginal basins.